Adesão às precauções padrão por trabalhadores de enfermagem de um hospital universitário: estudo de métodos mistos - Cunha, Quézia Boeira da (2016)
Nursing workers, especially those working in a hospital environment, are exposed daily to biological risks due to frequent contact with blood, secretions and other organic fluids. It is necessary that these workers adopt measures of protection, called standard precautions, in the care of each patient. The present study aimed to analyze individual, work - related and organizational factors related to adherence to the standard precautions of nursing workers at a University Hospital in the south of Brazil. It is characterized as a mixed method study with a concomitant data triangulation strategy. The investigation was carried out in a University Hospital of southern Brazil from July 2015 to June 2016. The research population was nursing workers from this setting - nurses, nursing technicians and nursing assistants - who worked in patient care units, both outpatient and inpatient. For data collection, a semi-structured interview and a research questionnaire containing two instruments were used: Sociodemographic and Professional Data Instrument and Instrument of Variables Relative to Standard Precautions. Twenty-four nursing workers were interviewed, among them: nine nurses, 11 nursing technicians and four nursing assistants. In the quantitative phase, 654 questionnaires were distributed, of which 602 were returned filled out in full. The analysis of the qualitative data was performed through the content analysis proposed by Bardin, and the analysis of the quantitative data was performed in the program PASW Statistics version 18.0. The majority of the participants, 519 (87.5%), were female and concentrated in the age group from 31 to 40 years, of which 186 (31.3%) were nurses; 324 (54.4%) nursing technicians and, 85 (14.3%), nursing assistants. The results obtained in the present study pointed out that adherence to standard precautions by nursing staff of the institution under investigation is partially affected and is influenced by individual factors, factors related to work and organizational factors. Quantitative data showed a positive and significant linear correlation between adherence to the standard precautions and these factors, which was corroborated with the qualitative data produced with the interviews. As for the individual, it was found that the age group 41-50 years and have received training on standard precautions at the hospital significantly influenced the adherence to standard precautions. Regarding the factors related to work, some obstacles to follow the PP were identified, such as: loss of manual dexterity with the use of Personal Protective Equipment, discomfort in using these equipment, prioritization of patient needs in detriment of professional safety, haste, among other issues. Organizational factors also pointed to the workers' adhesion, indicating some institutional actions that could be improved to promote safety practices. Changing the behavior of health professionals poses a major challenge for government agencies, managers and the workers themselves. So, some targets can be set for overcoming the difficulties now checked. Further follow-up investigations are suggested to evaluate the evolution of the adoption of safety practices.